The association between reproductive history and menopausal symptoms: an evidence from the cross-sectional survey - Seyedeh Hajar Sharami; Roya Faraji Darkhaneh; Nasrin Ghanami Gashti; Mandana Mansour-Ghanaei; Sedighe Bab Eghbal (BMC, 2022)
Abstract Background During menopause, women experience annoying symptoms which may affect their daily activities and quality of life. This study aimed to determine whether reproductive history, an important indicator of estrogen exposure across the lifetime, is associated with the severity of menopausal symptoms in women. Methods This study was a cross-sectional study conducted on 214 women aged 35-65 who were randomly selected, and data was collected by a predesigned structured questionnaire. Each item was graded by subjects and a total score was obtained by summing all subscale scores. Results There was a significant association between the somatic, psychological, and urogenital menopausal symptoms and reproductive characteristics. Women with a history of abortion had greater total (β = 0.194, p = 0.009), and psychological (β = 0.230, p = 0.002) symptoms score. Women with higher number of children were more likely to have higher somatic (β = 0.212, p = 0.005) symptoms than others. Conclusions Our findings showed reproductive factors may have an influence on the severity of menopausal symptoms. After confirmation by further studies, these findings may help target women at risk of more severe menopausal symptoms at later ages.